A new genus and a new species of pygmy mole cricket in Cretaceous amber from Burma (Orthoptera: Tridactylidae) - Cao, Cheng-Quan; Chen, Shen-Zhi; Yin, Zhan (Zootaxa, 2019)
A new genus and a new species of pygmy mole cricket i.e. Paraxya gen nov. and Paraxya hui sp. nov. are described from Burma Cretaceous amber in this paper. The new genus is allied to Xya Latreille. 1809, but differs from latter by lacking swimming plates at metatibia [Latreille. 1809; Yin et al, 1996; Cao et al, 2017, Cao et al, 2018 and Zhang et al, 2018]. The new genus is also allied to Burmadactylus Heads, 2009, but differs from latter by metatarsus absent and hindwing present, surpassing the end of abdomen distinctly [Heads, 2009]. Type specimen is deposited in the College of Life Science, Leshan Normal University, Leshan 614004, China.